METHODOLOGY OF USING "CASE STUDY" TECHNOLOGY IN ENGLISH CLASSES - Sayilova Mukhabbat Yangibayevna (Journals Park Publishing, 2024)
The article examines the notion potential of using the case study teaching method as one of the innovative ways of teaching English as a second language to high school students. The case study method contributes to the formation and development of systemic, conceptual knowledge, analytical thinking, communication skills, as well as the skills of structuring information presented to students and establishing cause-and-effect relationships in senior schoolchildren.
Keywords: case study, method, interactive teaching, English, high school students.